2012
DOI: 10.3109/02699052.2012.661911
|View full text |Cite
|
Sign up to set email alerts
|

Early motor predictors of recovery in patients with severe traumatic brain injury

Abstract: Head turning, together with or immediately followed by visual pursuit and fixation, proved to be clinically significant variables associated with recovery from vegetative state to higher states of consciousness beyond minimally conscious state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Some recent data show that, in the course of emerging from VS/ UWS towards MCS, visual pursuit, along with or immediately preceded by head control and head turning, are associated with better outcome [41]. Because visual pursuit assessment relies on an examiner's observation of a patient's eye movements, which might not be obvious, the use of quantitative assessment systems, such as eye-tracking systems, should be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent data show that, in the course of emerging from VS/ UWS towards MCS, visual pursuit, along with or immediately preceded by head control and head turning, are associated with better outcome [41]. Because visual pursuit assessment relies on an examiner's observation of a patient's eye movements, which might not be obvious, the use of quantitative assessment systems, such as eye-tracking systems, should be useful.…”
Section: Discussionmentioning
confidence: 99%
“…In this study cohort, no patients rated 3 (a result denoting MCS with intelligible verbalization) and low agreement (28%) was observed on reflex movements for scores of 1 and 2. Frequently, patients with disorders of consciousness may present different oromandibular movements including suction, chewing, bruxism or generating guttural vocal sounds [14]. All these responses represent forms of reflex movement and may give rise to score discrepancies, as raters may assign them 1 or 2 points on the oromotor scale.…”
Section: Discussionmentioning
confidence: 99%
“…Tamashiro et al investigated head control and turning, visual fixation and pursuit, and trunk movement and control in patients with TBIs and reported that significantly better results were achieved by the patients who were in a coma for a shorter period 25 ) .…”
Section: Discussionmentioning
confidence: 99%